2009
DOI: 10.1080/09297040902748226
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effort During Neuropsychological Evaluation with the TOMM in Children and Adolescents with Epilepsy

Abstract: Effort assessment is of particular importance in pediatric epilepsy where neuropsychological findings may influence treatment decisions, especially if surgical interventions are being considered. The present investigation examines the Test of Memory Malingering (TOMM) in 60 children and adolescents with epilepsy. The overall pass rate for the sample was 90%. TOMM scores were unrelated to age, though there was a significant correlation between TOMM Trial 2 scores and intelligence estimates. Overall, the TOMM ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…Despite the fact that the vast majority of children can pass the TOMM, there were statistically significant correlations between all TOMM trials and age, grade, intelligence, and memory. The current study correlations are similar to those found by MacAllister et al (2009), who documented a significant relationship between IQ and TOMM performance for Trials 1 and 2 and those found by Donders (2005), who documented a significant relationship between age and TOMM performance for Trials 1 and 2. In contrast to Donders (2005), we found a statistically significant relationship between CVLT-C memory performance and Trial 2 of the TOMM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the fact that the vast majority of children can pass the TOMM, there were statistically significant correlations between all TOMM trials and age, grade, intelligence, and memory. The current study correlations are similar to those found by MacAllister et al (2009), who documented a significant relationship between IQ and TOMM performance for Trials 1 and 2 and those found by Donders (2005), who documented a significant relationship between age and TOMM performance for Trials 1 and 2. In contrast to Donders (2005), we found a statistically significant relationship between CVLT-C memory performance and Trial 2 of the TOMM.…”
Section: Discussionsupporting
confidence: 92%
“…To date, there have been relatively few studies investigating the use of the TOMM in pediatric clinical populations, with the current literature supporting the use of the TOMM in patient populations as young as 6 years of age (Donders, 2005;MacAllister et al, 2009) and as a young as 5 years of age among typically developing children (Constantinou & McCaffrey, 2003). The current study revealed similar findings, suggesting that the TOMM is appropriate for use with pediatric clinical populations.…”
Section: Discussionsupporting
confidence: 88%
“…Regardless of whether a provider has a complete understanding of why a child fails an SVT, such performance should raise questions about the validity of all collected data, particularly if there is not evidence for genuine, significant impairment that could reasonably account for the results (MacAllister et al, 2009). As has been discussed in the adult literature, SVT failure cannot be equated with malingering.…”
Section: Discussionmentioning
confidence: 96%
“…When Donders (2005) examined the performance of 100 general pediatric patients on the Test of Memory Malingering (TOMM), he found two boys with a history of noncompliant behavior who were thought to be putting forth insufficient effort. MacAllister, Nakhutina, Bender, Karantzoulis, and Carlson (2009) reported that 2 out of 60 pediatric epilepsy patients performed poorly on the TOMM because of effort-related problems, rather than seizure-related impairment. Similarly, in a study by Carone (2008) Higher rates of response bias have been found in two additional pediatric case series, one of which included a population with a clear external incentive to perform poorly and one of which did not.…”
Section: Pediatric Noncredible Effort 605mentioning
confidence: 99%
See 1 more Smart Citation